Effect of Alcaligenes sp. on corrosion behavior of X65 steel in simulated offshore oilfield-produced water - Shi, Peiyu; Du, Min; Wang, Jian (Frontiers in Microbiology, 2023)
In this paper, the effect of Alcaligenes.sp on the corrosion process of X65 steel was investigated by using non-targeted metabolomics techniques for comprehensive characterization of metabolites, combined with surface analysis techniques and electrochemical testing. The results showed that the organic acids produced by Alcaligenes.sp accelerated the corrosion process of X65 steel in the early stage, and the presence of Alcaligenes.sp promoted the deposition of stable corrosion products and minerals in the middle and late stages. In addition, proteoglycans and corrosion inhibiting substances were enriched on the metal surface, which enhanced the stability of the film. The combined effect of multiple factors makes the mixed film of biofilm and corrosion products more dense and complete, which effectively inhibits the corrosion of X65 steel.